2012
DOI: 10.5114/pwki.2012.30400
|View full text |Cite
|
Sign up to set email alerts
|

The effect of superficial femoral artery stenting and some atherosclerosis risk factors on changes in selected global endothelial function tests in patients with chronic lower limb ischemia. A pilot study

Abstract: A b s t r a c tIntroduction: Endothelial dysfunction is the main pathomechanism of atherosclerotic processes and their complications. Revascularization and control of atherosclerosis risk factors may improve the global endothelial function.Aim: Assessment of the relationships between the level of selected atherosclerosis risk factors and changes in noninvasive endothelial function parameters during one year long follow-up after superficial femoral artery (SFA) stenting.Material and methods: Seventeen male pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, Budzyński et al reported that superficial femoral artery (SFA) stenting and classical pharmacotherapy did not significantly modify systemic endothelial function, as assessed by FMD in patients with adequately controlled individual risk factors of atherosclerosis. In contrast, among patients who did not reach treatment targets before SFA stenting, in those who underwent intensification of pharmacotherapy prior to the endovascular procedure, noticeable improvement in endothelial function markers (FMD, IMT) was observed within 3-6 months of observation [33].…”
Section: Discussionmentioning
confidence: 87%
“…On the other hand, Budzyński et al reported that superficial femoral artery (SFA) stenting and classical pharmacotherapy did not significantly modify systemic endothelial function, as assessed by FMD in patients with adequately controlled individual risk factors of atherosclerosis. In contrast, among patients who did not reach treatment targets before SFA stenting, in those who underwent intensification of pharmacotherapy prior to the endovascular procedure, noticeable improvement in endothelial function markers (FMD, IMT) was observed within 3-6 months of observation [33].…”
Section: Discussionmentioning
confidence: 87%